Preparation of an Injectable Macroporous α-TCP Cement - Vásquez Niño,Andrés Felipe (2016)
Abstract One of the most important characteristics of calcium phosphate cements is their resorbability when implanted in the body. However, the in vivo resorption rate is slow due to the lack of intrinsic open porosity. In this study, macroporous structures were obtained by mixing alpha-tricalcium phosphate (α-TCP) cement with a foamed liquid phase containing different concentrations of sodium hydrogen phosphate and non-ionic (Lutensol) or anionic (Sodium Lauryl Sulfate) surfactant. The cement paste was prepared by hand mixing in a system of two syringes connected by a polyvinyl chloride (PVC) valve, an environmentally friendly method. Solutions with Lutensol (L110) showed greater foamability than solutions with Sodium Lauryl Sulfate (SLS). Scanning Electron Microscopy characterization helped verify that the prepared samples showed a macroporous interconnected structure, and X-ray diffraction analysis evidenced the transformation of α-TCP into calcium deficient hydroxyapatite (CDHA). This study suggests that the calcium phosphate cement samples foamed with Lutensol may be further evaluated as suitable materials for bone filling.